Exploring the world of copywriting and content developing at Roar বাাংলা, during a global pandemic - Prana, Bijoya Shawrat (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022